Preparação de um novo catalisador de cobre trocado em zeólita magneticamente recuperável para síntese de 1,2,3-triazóis 1,4-dissubstituídos - Costa, Elizama Ramos (Universidade Federal de São Carlos, 2018)
The search for more sustainable methodologies has led in recent years to a significant increase in the development of more efficient heterogeneous catalysts, easily recoverable and with high stability over several reaction cycles. In this approach, zeolites emerge as a promising alternative for a wide range of reactions in organic synthesis, since they have unique physico-chemical characteristics, such as high acidity, presence of microporosity and also for acting as supports for catalysts prepared by ion exchange, it being possible then, the insertion of several metallic cations in their exchange sites. From this perspective, this work developed a catalyst exchanged with copper in zeolite β with magnetic support of ү-Fe2O3 that allows an easy and efficient separation of the catalyst from the reaction medium. After synthesis, the catalyst was characterized by X-ray diffraction (XRD), transmission electron microscopy (MET), atomic emission spectroscopy (ICP-OES), X-ray flowering (FRX), excited photoelectron spectroscopy (XPS). The magnetically recoverable copper catalyst (ү-Fe2O3-β-Cu(I)) was used in the synthesis of 1,2,3-1,4-disubstituted triazoles in a multicomponent approach with formation of azide in situ using water as a solvent. The optimization of the reaction conditions was performed using the benzyl bromide, sodium azide and phenylacetylene reagents as model substrates. In the optimization stage, different reaction parameters were evaluated, such as temperature, time, solvent and amount of catalyst. With the result of the optimization in hand, a study was carried out on the scope of the reaction, where the products were obtained with good to excellent yields. At the end of the synthesis, a study was carried out on the recovery of the catalyst, being possible its reuse for up to 5 reaction cycles leading to triazoles in good yields.
Preparation of a new copper catalyst replaced in magnetically recoverable zeolite for synthesis of 1,2,3-triazoles 1,4-dissubstituted
Keywords: Zeólita β; Suporte magnético; Água; 1,2,3-Triazóis; Zeolite β; Magnetic support; Water; 1,2,3-Triazoles; CIENCIAS EXATAS E DA TERRA::QUIMICA